Meta Analysis Study of Factors Relates Eating Disorders on Adolescents - Azrimaidaliza Azrimaidaliza; Helmizar Helmizar; Ferina Yollanda (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2021)
Eating disorders are one of the nutritional problems that occur on adolescents, especially in Indonesia. Various factors can cause eating disorders in adolescents. Research on factors related to eating disorders on adolescents has been available in Indonesia, but the results were varied, some were related and some were not. This research objective was to determine the factors relates with eating disorders on adolescents in Indonesia. Research methods with quantitative design and meta-analysis analysis techniques. This article is looking through PubMed, DOAJ, Garuda Portal, Google Scholar, and ISJD databases with time limits from 2000-2020. Data processing is done with the RevMan 5.4 application. The results obtained were 2,453 articles identified, there were 13 studies that were systematically reviewed and followed by a meta-analysis. A negative body image has a 3.40 times (95% CI 1.71-6.78) risk of eating disorders on adolescents. There is no significant correlation between nutritional knowledge, peers, and the mass media with eating disorders on adolescents in Indonesia. Body image is one of the factors for eating disorders on adolescents in Indonesia. It is expected that adolescents will adopt a healthy lifestyle and good eating behavior in order to get a positive body image and avoid eating disorders. Abstrak: Gangguan makan merupakan salah satu masalah gizi yang terjadi pada remaja terutama di Indonesia. Berbagai faktor dapat menyebabkan gangguan makan pada remaja. Penelitian mengenai faktor yang berhubungan dengan gangguan makan pada remaja sudah terdapat di Indonesia, tetapi didapatkan hasil yang bervariasi, ada yang berhubungan dan ada yang tidak berhubungan. Penelitian ini bertujuan untuk mengetahui faktor-faktor yang berhubungan dengan gangguan makan pada remaja di Indonesia. Metode penelitian dengan desain kuantitatif dan teknik analisis meta-analisis. Penelusuran melalui database PubMed, DOAJ, Portal Garuda, Google Schoolar, dan ISJD dengan batasan waktu dari tahun 2000-2020. Pengolahan data dilakukan dengan aplikasi RevMan 5.4. Hasil yang didapatkan sebanyak 2.453 artikel yang diidentifikasi, terdapat 13 penelitian yang ditelaah sistematis dan dilanjutkan dengan meta-analisis. Citra tubuh yang negatif berisiko 3,40 kali (95% CI 1,71-6,78) mengalami gangguan makan pada remaja. Tidak adanya hubungan yang signifikan antara pengetahuan gizi, teman sebaya, dan media massa  dengan gangguan makan pada remaja di Indonesia. Citra tubuh merupakan salah satu faktor gangguan makan pada remaja di Indonesia. Diharapkan kepada remaja untuk menerapkan pola hidup yang sehat dan perilaku makan yang baik  agar mendapatkan citra tubuh yang positif dan terhindar dari gangguan makan.